LABORATORIUM PAUD SEBAGAI SUMBER BELAJAR BAGI MAHASISWA (STUDI KASUS PADA MAHASISWA PG-PAUD UNIVERSITAS MUHAMMADIYAH PONOROGO) - Nuryanto, Sidik (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2018)
Laboratory (Lab) PG-PAUD Muhammadiyah University Of Ponorogo as a place for students to conduct experiments, innovate creativity, make products so that they become a person who is scientific. This qualitative research aims to find out the function of laboratory use, collections, and constraints faced. Information sources of students, laboratory staff, lecturers and data collection techniques with observation, interviews, documentation and instruments The validity of the data with trust, transfer, dependency and certainty. Analysis with the stages of data collection, data reduction, data presentation, and conclusion drawing. The result is the laboratory function as a place for lectures and production, laboratory collections in the form of messages, people, equipment materials and settings, while the constraints are in the form of facilities and infrastructure, materials and learning resources, and managementKeywords: PG-PAUD Laboratory, Learning Resources, PG-PAUD Students